GEOCHEMISTRY OF MACROELEMENTS IN THE SANDY LANDSCAPES OF CENTRAL FERGANA (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The study investigates the geochemical composition and macroelement dynamics of the sandy soils in the Chinobod area, Dangara District, Fergana Region. The research aims to evaluate the distribution, mobility, and ecological significance of key macroelements (Ca, Fe, K, Na, and Ba) under natural and anthropogenic influences. Soil samples were collected using the morphogenetic profiling method developed by V. V. Dokuchaev, while elemental analysis was performed by neutron activation analysis (NAA) to ensure high accuracy and multi-element detection. The obtained results revealed minimal vertical differentiation of macroelements, with concentrations ranging between 9.7 and 16.0 mg/kg. The sequence of abundance (Ca > Fe > K > Na > Ba) reflects the predominance of carbonate minerals and the stability of oxidation–reduction processes in the arid sandy landscapes of Central Fergana. The study confirms the homogeneity of parent materials, the dominance of natural pedogenic processes, and weak anthropogenic impact. These findings provide a scientific basis for developing an integrated geochemical monitoring system and for ensuring the sustainable management of fragile sandy ecosystems in the Fergana Valley.